Causes of The occurrence of Obstacles in The Implementation of âNormal Labor Attendanceâ Skills Lab for Midwifery Students at Institute of Health Science "Surya Mitra Husada Kediri" - Siwi, Retno Palupi Yonni (Health Notions, 2017)
This study aimed to analyze the factors that influence the occurrence of obstacles in the skills lab about Normal Labor Attendance for the students in midwifery school of Institute of Health Sciences "Surya Mitra Husada" Kediri, with cross sectional design. The subjects were 37 students of Semester IV, selected using total sampling technique. Factors studied were mentor roles, interest in learning, and tool limitations. Data were collected through questionnaires and observation sheets, then analyzed using ordinal regression test. The p-value of the ordinal regression test was 0.000; so it was concluded that the mentor roles, interest in learning and tool limitations affected the occurrence of obstacles in the skills lab.